Ruínas do sertão e dos sertanejos: identidades possíveis em Faca, de Ronaldo Correia de Brito - Bessa, Alessandra Zelinda Sousa (2018)
In the short stories of Brito (2003), especifically on his work Faca, we find characters from Inhamuns hinterland, known in inner part of his memories and how they manifest his acts before family group. Eleven plots that develop in the very cearense land and through them, it is possible to point out predominance of social segregation among subjects of same collectivity; the return to past; feminine autonomy, living with patriarchalism; gypsies presence, mysterious men; women performance among other factors that circumscribe men in such a space. The goal of this research was to demonstrate how myths from the hinterland and locals are capable of guiding acts of characters of the book Faca. As bibliographical basis, some of authors mentioned were: Agamben (2005), Albuquerque Jr. (1999), Bhabha (1998), Deleuze, G., Guattari. F. (1977), Dalcastagnè (2005), Eliade (2011), Halbwachs (2006), Haesbaert (2004), Schollammer (2011), Sodré (2002), Santini (2009) e Vicentini (2007). The analysis used the concept of “Agamben Dispositif” (2005) and notion of “minor language” of Deleuze and Guattari (1977). Various themes were called, so, to the dialogue in order to expand the approaches such as collective memory (influencer of characters behavior), the imaginary as a former of Northeast and resignification of old hinterland costums. We tried, therefore, to contribute to analysis of issues of northeast hinterland in literature as well as to provide motivational thoughts of other researches on Ronaldo Correia de Brito works. We could confirm that author’s literaty production present a polyphony resulting of multiple knowledge on men and nature. One of those manifestations justifies itself by the reflexes on his work, on his own life, time and space in which he lived.